2015
DOI: 10.18093/0869-0189-2015-25-4-425-432
|View full text |Cite
|
Sign up to set email alerts
|

Genetic features of patients with influenza A / H1N1 / 09 complicated by pneumonia

Abstract: Целью исследования явилось выявление особенностей полиморфизмов генов цитокинов (фактор некроза опухоли-TNF G308A, ин терлейкины-IL 10 C592A, IL 10 C819T, IL 10 G1082A), гена регуляторной молекулы воспаления (CD14 C159T) и регуляции сосудис того тонуса (еNOS C786T) у пациентов с гриппом A / H1N1, осложненном пневмонией. Материалы и методы. Обследованы пациен ты, находившиеся на лечении по поводу пневмонии на фоне гриппа А / H1N1 / 09: 1 я группа (n = 37)-с тяжелыми пневмониями; 2 я (n = 74)-с нетяжелыми пневмо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Through experimental and clinical studies, the systemic inflammatory dysregulation correlating with the disease’s severity and progression has been identified as one of the most important pathogenic mechanisms in infection [ 11 , 12 ]. Cytokine secretion by infected cells is necessary for the initiation of the immune response that controls virus replication [ 13 ]; also, immunopathological mechanisms such as hypercytokinemia (also known as cytokine storm) generally contribute to the more severe evolution of the infection [ 14 , 15 ].…”
Section: Inflammatory Response and Ifitm3 Role In Influenza A Virumentioning
confidence: 99%
“…Through experimental and clinical studies, the systemic inflammatory dysregulation correlating with the disease’s severity and progression has been identified as one of the most important pathogenic mechanisms in infection [ 11 , 12 ]. Cytokine secretion by infected cells is necessary for the initiation of the immune response that controls virus replication [ 13 ]; also, immunopathological mechanisms such as hypercytokinemia (also known as cytokine storm) generally contribute to the more severe evolution of the infection [ 14 , 15 ].…”
Section: Inflammatory Response and Ifitm3 Role In Influenza A Virumentioning
confidence: 99%
“…Viruses take advantage of SNPs-driven variations in host cytokines that alter the transcriptional activity of their genes as well as association with the possibility of a wide range of influenza viruses [30]. Another challenge is monitoring or classifying people with influenza-like illness [31] that frequently occur after influenza virus vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the finding reported by a study of patients with influenza pandemic (H1N1) wherein the frequencies of "A" allele and GA genotype were significantly lower while those of the G allele and GG genotype were significantly higher among patients compared with controls [18]. Similarly, another study reported that the patients with influenza-related pneumonia were more frequently homozygous for the G allele of the TNF 308 G/A polymorphism compared with controls [19].…”
Section: Discussionmentioning
confidence: 69%